World Environmental and Water Resources Congress 2015 2015
DOI: 10.1061/9780784479162.236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Passive Treatment Technologies for Septic Lagoon Capacity Expansion

Abstract: This research was conducted independently by the author and under the supervision of Dr. Pascale Champagne, who has reviewed and edited this thesis. All experimental work and results were obtained through her technical guidance and feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Several technologies have been employed to upgrade lagoons, such as extended aeration of aerated lagoons (Melcer et al, 1995), trickling filters (Archer & O’Brien, 2005; Avsar et al, 2008), rotating biological contactors (RBCs) (Hassard et al, 2015) and constructed wetlands (Butterworth et al, 2016; Cameron et al, 2003). In recent years, studies have outlined the use of rock or aggregate‐based attached growth systems (Mara & Johnson, 2006; Mattson et al, 2018; Swanson & Williamson, 1980), stationary in‐lagoon fixed‐film media (Gan & Champagne, 2015; Shin & Polprasert, 1988; Srinivas, 2007) and moving bed biofilm reactor (MBBR) systems (Delatolla et al, 2010; Hoang, 2013; Wessman & Johnson, 2006) to upgrade lagoons either by enhancing microbially mediated nitrification or by increasing the lagoon system’s volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of nitrifying attached growth technologies, such as the MBBR to enhance TAN removal performance at the end of lagoons to meet stringent ammonia effluent guidelines at ultra‐low (0.6–3.0°C) temperatures (Ahmed et al, 2019; Almomani et al, 2014; Delatolla et al, 2010; Hoang, 2013; Patry et al, 2019; Young et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies have been employed to upgrade lagoons, such as extended aeration of aerated lagoons (Melcer et al, 1995), trickling filters (Archer & O’Brien, 2005; Avsar et al, 2008), rotating biological contactors (RBCs) (Hassard et al, 2015) and constructed wetlands (Butterworth et al, 2016; Cameron et al, 2003). In recent years, studies have outlined the use of rock or aggregate‐based attached growth systems (Mara & Johnson, 2006; Mattson et al, 2018; Swanson & Williamson, 1980), stationary in‐lagoon fixed‐film media (Gan & Champagne, 2015; Shin & Polprasert, 1988; Srinivas, 2007) and moving bed biofilm reactor (MBBR) systems (Delatolla et al, 2010; Hoang, 2013; Wessman & Johnson, 2006) to upgrade lagoons either by enhancing microbially mediated nitrification or by increasing the lagoon system’s volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of nitrifying attached growth technologies, such as the MBBR to enhance TAN removal performance at the end of lagoons to meet stringent ammonia effluent guidelines at ultra‐low (0.6–3.0°C) temperatures (Ahmed et al, 2019; Almomani et al, 2014; Delatolla et al, 2010; Hoang, 2013; Patry et al, 2019; Young et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies have been employed to upgrade lagoons; such as extended aeration of aerated lagoons (Melcer et al, 1995), trickling filters (Archer and O'Brien, 2005;Avsar et al, 2008), rotating biological contactors (RBC) (Hassard et al, 2015), and constructed wetlands (Cameron et al, 2003;Butterworth et al, 2016). In recent years, studies have outlined the use of rock or aggregate-based attached growth systems (Swanson and Williamson, 1980;Mara and Johnson, 2006;Mattson et al, 2018), stationary in-lagoon fixed film media (Shin and Polprasert, 1988;Srinivas, 2007;Gan and Champagne, 2015) and MBBR systems (Wessman and Johnson, 2006;Delatolla et al, 2010;Hoang, 2013) to upgrade lagoons either by enhancing microbially-mediated nitrification or by increasing the lagoon system's volumetric or loading capacity. Numerous studies have recently demonstrated the effectiveness of attached growth nitrification systems to enhance TAN-removal performance in lagoons to meet stringent ammonia effluent guidelines at ultra-low (0.6 -3.0°C) temperatures (Delatolla et al, 2010;Hoang, 2013;Almomani et al, 2014;Young et al, 2016b;Ahmed et al, 2019;Patry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%